The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12144-022-03718-3
|View full text |Cite
|
Sign up to set email alerts
|

Good can be stronger than bad: the daily relationship among maternal warmth, mother-teen conflict and adolescents’ self-esteem

Abstract: Self-esteem is associated with adaptive adolescent outcomes but tends to decline in adolescence. Parent-teen warmth has been linked to concurrent increases in adolescents' self-esteem while adolescents' conflict with parents is detrimental to their self-esteem in cross-sectional or longitudinal studies. However, it is unknown how adolescents experience of maternal warmth and conflict with mothers are correlated with their daily self-esteem, and whether these associations vary in adolescents' gender, age and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Differences in parenting, regardless of form, may spur social comparisons between siblings (Jensen et al, 2015;Scholte et al, 2007) or may engender family conflict and strife (Kowal et al, 2004;Kowal & Kramer, 1997). This finding is in stark contrast to research on parenting in general which suggests that some domains may be more salient than others (Coffey et al, 2022;Lam et al, 2018;Wu et al, 2022). More work will need to continue in this area and examine how perceptions of fairness (Kowal et al, 2002;Kowal & Kramer, 1997) may further interact with the domain of parenting.…”
Section: Moderating Contextsmentioning
confidence: 96%
See 1 more Smart Citation
“…Differences in parenting, regardless of form, may spur social comparisons between siblings (Jensen et al, 2015;Scholte et al, 2007) or may engender family conflict and strife (Kowal et al, 2004;Kowal & Kramer, 1997). This finding is in stark contrast to research on parenting in general which suggests that some domains may be more salient than others (Coffey et al, 2022;Lam et al, 2018;Wu et al, 2022). More work will need to continue in this area and examine how perceptions of fairness (Kowal et al, 2002;Kowal & Kramer, 1997) may further interact with the domain of parenting.…”
Section: Moderating Contextsmentioning
confidence: 96%
“…These include affection (Atzaba-Poria & Pike, 2008;Shanahan et al, 2008), conflict (Feinberg & Hetherington, 2001;Shanahan et al, 2008), resources (Jensen et al, 2013;McHale et al, 2005), control or autonomy (Sheehan & Noller, 2002;Tamrouti-Makkink et al, 2004), and measures focused on overall PDT (Coldwell et al, 2008;Rolan & Marceau, 2018). The broader parenting literature suggests that not all aspects of parenting are equal in their links with child and adolescent outcomes (Coffey et al, 2022;Lam et al, 2018;Wu et al, 2022). For example, Dhondt et al (2019) found that parental conflict was linked to more internalizing and externalizing behavior among children and adolescents, but parental positivity was not at all linked to those behaviors.…”
Section: Domain Of Parentingmentioning
confidence: 99%